Simbol Masyarakat Sufistik: Studi Peran Majelis Dzikir Al-Khidmah - Muhammad Nur Hakim; Akhmad Sirojuddin; Ari Kartiko (Indonesian Journal of Humanities and Social Sciences, 2023)
This research was carried out to find symbols of Sufism through the Al-Khidmah dhikr assembly, which has been carried out for a long time by the people of Talang Prigen Pasuruan hamlet; this research is to complement the previous study, which focused on urban Sufism and the Al-Khidmah dhikr assembly as a solution to moral improvement teenagers, family and other social interests of society, symbols in a particular society. This research methodology uses a descriptive qualitative approach, field research type, through observation tests and informant interviews to find the objectivity of the data and, at the same time, discuss the analysis as data validation. The findings produced are 1) Organizational symbols as a medium for serving the congregation, 2) Sosial building humanism as a symbol of community social identity, and 3) Symbols of education and teaching in the form of ruhiyah amaliyah routines that are binding for every individual and congregation who have carried out the oath of allegiance.